DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP MOTIVASI DAN PRESTASI AKADEMIK SISWA TEKNIK OTOMOTIF: STUDI EMPIRIS DI SEKOLAH MENENGAH KEJURUAN - Alyauma Fuadi; Toto Sugiarto; Wagino Wagino; Hendra Dani Saputra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The digital era has transformed the learning paradigm in vocational high schools, particularly in the field of automotive engineering. Social media has now become an integral part of students' lives, which can affect their motivation and academic achievement. This study aims to analyze the impact of social media use on learning motivation and academic achievement of automotive engineering students in vocational high schools. Quantitative research with a causal-comparative design was conducted on 71 grade XI Light Vehicle Engineering students at SMKN 1 Padang. Data were collected through structured questionnaires and academic grade documentation. Data analysis used MANOVA with Hotelling's Trace test statistics to test simultaneous effects. The results showed that social media had a positive and significant effect on students' learning motivation (F = 31.004, p 0.05), but did not significantly affect their academic achievement (F = 0.610, p 0.05). Simultaneously, social media use did not show a significant effect on the combination of learning motivation and academic achievement (Hotelling's Trace = 8.880; F = 1.421; p = 0.223). While social media can increase automotive engineering students' motivation to learn, its impact on academic achievement is less than optimal. A more targeted strategy for utilizing social media and integrating it with the curriculum is needed to maximize its potential in supporting automotive engineering learning.Keywords: Social Media, Learning Motivation, Academic Achievement, Automotive Engineering, Vocational Education.